2016
DOI: 10.1021/acs.estlett.6b00105
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Viruses in Wastewater Systems and Potential for Aerosolization

Abstract: To gain insight into the potential for aerosolization of viruses in wastewater systems, we investigated the partitioning of MS2 and Phi6 bacteriophages in synthetic sludge and anaerobically digested sludge from a wastewater treatment plant. We evaluated partitioning among the liquid, solids, and material surfaces of porcelain, concrete, polyvinyl chloride (PVC), and polypropylene. In all cases, at least 94% of the virions partitioned into the liquid fraction. In real sludge, no more than 0.8% of virions partit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…the actual Ct would in fact be less than the modeled Ct for the evaluated conditions and viral inactivation would be more rapid than reported. Due to the dilute nature of the wastewater evaluated, the role of higher organic loading and particle association in protecting virus from disinfection remains unresolved, although recent studies using Ebola virus surrogates have suggested that the majority (~90%) of viral particles remain not particle associated [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…the actual Ct would in fact be less than the modeled Ct for the evaluated conditions and viral inactivation would be more rapid than reported. Due to the dilute nature of the wastewater evaluated, the role of higher organic loading and particle association in protecting virus from disinfection remains unresolved, although recent studies using Ebola virus surrogates have suggested that the majority (~90%) of viral particles remain not particle associated [ 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Phage Phi6 and its bacterial host Pseudomonas syringae were kindly provided by Dr. Krista Wigginton's lab at University of Michigan. Pseudomonas phage Phi6 has been used as a model enveloped virus in virus recovery and persistence studies in wastewater and microdroplets ( Aquino de Carvalho et al, 2017 ; Fedorenko et al, 2020 ; Titcombe Lee et al, 2016 ; Ye et al, 2016 ). Phi6 was inoculated into 200 ml of wastewater samples at a concentration of 10 3 plaque forming unit per ml.…”
Section: Methodsmentioning
confidence: 99%
“…Even before the current pandemic, the aerosolization of wastewater systems was studied for its potential role in the viruses’ transmission ( Lee et al, 2016 ). Beyond the fecal-oral route, the aerosolized water that is contaminated by SARS-CoV-2 can be the much more dangerous transmission route ( de Oliveira et al, 2021 ).…”
Section: A Critical Review Of Related Studiesmentioning
confidence: 99%